2001
DOI: 10.1001/archsurg.136.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Histological Grade of Hepatocellular Carcinoma on the Outcome of Liver Transplantation

Abstract: Histological grade of hepatocellular carcinoma (HCC) is an important prognostic factor affecting patient survival after orthotopic liver transplantation (OLT).Design: Retrospective analysis.Setting: University-based teaching hospital.Patients: Of 952 OLTs performed between June 1991 and January 1999, 56 OLT recipients had histologically proven HCC in the explant liver. Of those, 53 patients with complete clinicopathologic data were analyzed. A single pathologist blinded to the outcome of each patient reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
153
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(179 citation statements)
references
References 36 publications
11
153
2
Order By: Relevance
“…Furthermore, the Pittsburgh group observed that in 30% of the cases, the same combination of tumor characteristics in their prognostic model did not correlate well with clinical outcome as predicted. 19 Several published studies have found poorly differentiated histologic grade, 17,20,21 or microvascular invasion, 11,22 or both 23 to be independent predictors of impaired survival after OLT. The present study suggests a strong correlation of these histologic features with more advanced tumor stage exceeding the limits of the Milan and UCSF criteria, albeit to a lesser degree for the latter (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Pittsburgh group observed that in 30% of the cases, the same combination of tumor characteristics in their prognostic model did not correlate well with clinical outcome as predicted. 19 Several published studies have found poorly differentiated histologic grade, 17,20,21 or microvascular invasion, 11,22 or both 23 to be independent predictors of impaired survival after OLT. The present study suggests a strong correlation of these histologic features with more advanced tumor stage exceeding the limits of the Milan and UCSF criteria, albeit to a lesser degree for the latter (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the serum biomarkers alpha-fetoprotein (AFP) and protein induced by vitamin K absence-II (PIVKA-II) are used as prognostic markers 7,8 and also as surrogate markers for microvascular invasion and tumor differentiation. 9,10 AFP is associated with grade differentiation, 11 whereas PIVKA-II is related to vascular invasion. 12,13 However, these tumor markers have limited sensitivity and are less predictive than microvascular invasion, 14,15 which is the most potent determinant of recurrence and survival in HCC patients undergoing a hepatectomy.…”
mentioning
confidence: 99%
“…Despite size, tumor volume, and absence of extrahepatic disease being the predominant factors in consideration of patients with HCC for LT, molecular, genetic markers, and markers of invasiveness may have a significant role to play in determining the outcomes after transplantation. Functional allelic imbalance [25], high tumor grade (G2 and G3) [26], and mVI [27] have been predictive of early recurrence without adjusting for tumor volume. The correlation between tumor volume and mVI has also not been consistently demonstrated to be linear.…”
Section: History and Evolution Of Liver Transplantation For Hccmentioning
confidence: 99%